Meningkatkan prestasi belajar bahasa Inggris melalui penerapan model pembelajaran problem based learning - I Nengah Nuarta (Indonesian Journal of Educational Development, 2020)
Analyzing social functions, text structure, and linguistic elements in expressions of offering services and responses according to the context of their use is one of the difficult materials for students. Data on learning achievement of learning material in recent years show that student achievement is very low, therefore it is necessary to find a solution. For this reason, classroom action research was conducted with the subject of the study was students of class XII IPS-2 of SMA Negeri 1 Marga in semester 1 of 2018/2019, with a total of 38 people. The object of this research is English learning achievement. The purpose of this study was to analyze the effectiveness of the problem based learning model to improve English learning achievement. Data were collected using a learning achievement test and analyzed descriptively qualitatively. This action research was successfulwhen it reached a minimum average value of 70 and a minimum 85% of mastery learning. The results of the study in the first cycle revealed that the average English learning achievement was 69.41 with a classical learning completeness of 78.94%. While in the second cycle, the average English learning achievement was 72.88 and the classical learning completeness was 89.47%. The application of the problem based learning model can improve the learning achievement of students of class XII IPS-2 SMA Negeri 1 Marga in odd academic year in two cycles. Menganalisis fungsi sosial, struktur teks, dan unsur kebahasaan pada ungkapan menawarkan jasa dan responnya sesuai dengan konteks penggunaanya merupakan satu diantara materi sulit bagi siswa. Data prestasi belajar materi tersebut dalam beberapa tahun terakhir menunjukkan prestasi siswa sangat rendah, sehingga perlu dicarikan solusinya. Untuk itu dilaksanakan penelitian tindakan kelas dengan subjek penelitian siswa kelas XII IPS-2 SMA Negeri 1 Marga semester 1 tahun pelajaran 2018/2019 yang berjumlah 38 orang. Objek penelitian adalah prestasi belajar bahasa Inggris. Tujuan penelitian adalah untuk mengetahuidan menganalisis efektivitas model PBL untuk meningkatkan prestasi belajar bahasa Inggris. Data dikumpulkan menggunakan tes prestasi belajar dan dianalisis secara deskriptif kualitatif. Penelitian tindakan ini dikatakan berhasil bila mencapai nilai rerata minimal 70 dan ketuntasan belaja klasikal minimal 85%. Hasil penelitian menunjukkan bahwa pada siklus I nilai rerata 69,41 dengan ketuntasan klasikal 78.94%. Sedangkan pada siklus II, nilai rerata sebesar 72,88 dan ketuntasan klasikal mencapai 89,47%. Penerapan model pembelajaran PBL dapat meningkatkan prestasi belajar siswa kelas XII IPS-2 SMA Negeri 1 Marga semester1 tahun pelajaran 2018/2019 dalam dua siklus.